2023
DOI: 10.1038/s41598-023-37271-1
|View full text |Cite
|
Sign up to set email alerts
|

Refining the serum miR-371a-3p test for viable germ cell tumor detection

Abstract: Circulating miR-371a-3p has excellent performance in the detection of viable (non-teratoma) germ cell tumor (GCT) pre-orchiectomy; however, its ability to detect occult disease is understudied. To refine the serum miR-371a-3p assay in the minimal residual disease setting we compared performance of raw (Cq) and normalized (∆Cq, RQ) values from prior assays, and validated interlaboratory concordance by aliquot swapping. Revised assay performance was determined in a cohort of 32 patients suspected of occult retro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Understanding the immense possibilities for use of circulating microRNAs is underway; however, a major hindrance could result from the current lack of standardized conventions used to collect, store, analyze, and interpret data. The development of an accepted protocol may limit obstacles, such as interlaboratory heterogeneity, allowing for widespread clinical use of circulating miRNA levels [34,35]. Current studies are gaining traction on this issue [28].…”
Section: Unrefined Standardized Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the immense possibilities for use of circulating microRNAs is underway; however, a major hindrance could result from the current lack of standardized conventions used to collect, store, analyze, and interpret data. The development of an accepted protocol may limit obstacles, such as interlaboratory heterogeneity, allowing for widespread clinical use of circulating miRNA levels [34,35]. Current studies are gaining traction on this issue [28].…”
Section: Unrefined Standardized Protocolsmentioning
confidence: 99%
“…Current studies are gaining traction on this issue [28]. Lafin et al suggested the use of raw Cq values from serum qPCR-based methods with pre-amplification after discovering the normalization process of assays increased the likelihood of variation and therefore heterogeneity [34]. The use of raw miR-371a-3p Cq data, in this context, is associated with lower cost, which can be useful for incorporation of miRNA analysis into routine clinical testing.…”
Section: Unrefined Standardized Protocolsmentioning
confidence: 99%